Search Engine Optimization with Google - Gunjan, Vinit Kumar; Pooja; Kumari, Monika; Kumar, Amit; Rao, Allam Appa (Asian Journal of Engineering and Applied Technology, 2012)
Search engine optimization is a strategical technique to take a web document in top search results of a search engine. Online presence of an organisation is not only an easy way to reach among the target users but it may be profitable too if optimization is done keeping in view of the target users as of the reason that most of the time users search out with the keywords of their use (Say; Ph.D in web technology) rather than searching the organisation name, and if the page link comes in the top positions then the page may be profitable. This work describes the tweaks of taking the page on top position in Google by increasing the Page rank which may result in the improved visibility and profitable deal for an organisation. Google is most user friendly search engine proved for the Indian users which gives user oriented results. In addition, most of other search engines use Google search patterns so we have concentrated on it. So, if a page is optimised in Google it is optimised for most of the search engines.